Black and indigenous : Garifuna activism and consumer culture in Honduras - Anderson, Mark, 1969- (University of Minnesota Press, 2009)
Garifuna live in Central America, primarily Honduras, and the United States. Identified as Black by others and by themselves, they also claim indigenous status and rights in Latin America. Examining this set of paradoxes, Mark Anderson shows how, on the one hand, Garifuna embrace discourses of tradition, roots, and a paradigm of ethnic political struggle. On the other hand, Garifuna often affirm blackness through assertions of African roots and affiliations with Blacks elsewhere, drawing particularly on popular images of U.S. blackness embodied by hip-hop music and culture. Black and Indigenous.